A Study on the Influence of FDM Parameters on the Tensile Behavior of Samples made of PET-G - Zisopol, Dragos Gabriel; Minescu, Mihail; Iacob, Dragos Valentin (Engineering, Technology & Applied Science Research, 2024)
This experimental study investigated the influence of FDM 3D printing parameters on the tensile behavior of PET-G-made parts. In this context, 27 test specimens were produced using FDM on the Anycubic 4 Max Pro 2.0 printer with layer heights applied in one pass Lh = 0.10/0.15/0.20 mm and filling percentages Id = 50/75/100 %. All these samples were tensile tested on the Barrus White 20 kN universal testing machine. The experimental results determined maximum tensile strength, elongation percentage at break, and Young’s modulus. The two parameters considered, Id and Lh, influence the maximum tensile strength, the elongation percentage at break, and Young’s modulus. The findings demonstrated that the filling percentage has a strong influence on the maximum tensile strength and the elongation percentage at the break of the PET-G samples, and Lh has a decisive influence on Young’s modulus.